An economic analysis of identity and career choice - Maria Knoth Humlum; Kristin J. Kleinjans; Helena Skyt Nielsen (Institute for the Study of Labor (IZA), 2007)
Standard economic models which focus on pecuniary payoffs cannot explain why there are highly able individuals who choose careers with low pecuniary returns. Therefore, financial incentives are unlikely to be effective in influencing career choices of these individuals. Based on Akerlof and Kranton (2000), we consider a model of career choice and identity where individuals derive non-pecuniary identity payoffs. Using factor analysis on a range of attitude questions, we find two factors related to identity (career orientation and social orientation), which are important for educational choices. The implication is that policymakers and institutions of higher education need to focus on identity related issues rather than just improved financial incentives if they aim at attracting the high ability youth to occupations with excess demand for labor.
Keywords: 330; Career choice; choice of higher education; identity; self-image; Persönlichkeitspsychologie; Sozialpsychologie; Bildungsverhalten; Karriereplanung; Erwerbsverlauf; Faktorenanalyse; Dänemark